Analysis of Factors Influencing Saving Behavior in Private Employees in Jombang - Zulfikar Khusnul Ghina Rizky; Tri Kartika Pertiwi; G. Oka Warmana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Financial stability plays a vital role in determining an individual’s overall well-being, and saving is considered one of the most fundamental practices for managing personal finances and preparing for future uncertainties. In many developing regions, the level of savings among employees remains relatively low, making it crucial to understand the factors that encourage or hinder saving behavior. This study aims to examine the influence of financial inclusion, lifestyle, and financial planning on the saving behavior of private sector employees in Jombang Regency, Indonesia. The research employed a quantitative approach by distributing structured questionnaires to 100 respondents who met the eligibility criteria. The participants were selected using a purposive sampling technique to ensure that only employees with sufficient financial exposure and employment stability were included. The instrument used a Likert-scale to measure perceptions and behaviors, and the data collected were analyzed using the Partial Least Squares (PLS) method with the assistance of SmartPLS version 3 software. The findings reveal that financial inclusion, lifestyle, and financial planning each exert a significant and positive effect on saving behavior. Employees who have greater access to financial services and products are more likely to engage in consistent saving practices. Likewise, individuals who adopt a prudent lifestyle and maintain effective financial planning demonstrate stronger saving discipline. These results underscore the importance of integrating financial literacy and planning strategies with broader financial inclusion programs. In conclusion, promoting financial inclusion, encouraging simple and sustainable lifestyle choices, and strengthening financial planning skills can collectively enhance saving behavior among employees. This study provides valuable insights for policymakers, financial institutions, and employers seeking to foster long-term financial resilience and economic security for the workforce.